The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/anie.201601881
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Non‐Specific and Specific Adhesive Interactions of Catechols at Solid/Liquid Interfaces at the Molecular Scale

Abstract: The adhesive system of mussels evolved into a powerful and adaptive system with affinity to a wide range of surfaces. It is widely known that thereby 3,4‐dihydroxyphenylalanine (Dopa) plays a central role. However underlying binding energies remain unknown at the single molecular scale. Here, we use single‐molecule force spectroscopy to estimate binding energies of single catechols with a large range of opposing chemical functionalities. Our data demonstrate significant interactions of Dopa with all functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…1). Although the presence of the catechol moiety is one important contributor to the process of underwater adhesion, [37][38][39][40][41][42] some other interactions must also be responsible for this rapid deposition onto the silicon surface, e.g. electrostatic or p-p stacking.…”
Section: Resultsmentioning
confidence: 99%
“…1). Although the presence of the catechol moiety is one important contributor to the process of underwater adhesion, [37][38][39][40][41][42] some other interactions must also be responsible for this rapid deposition onto the silicon surface, e.g. electrostatic or p-p stacking.…”
Section: Resultsmentioning
confidence: 99%
“…The forces logarithmically depended on the loading rates. The experimental condition-dependent rupture forces were further exemplied by Utzig et al, 113 Kinugawa et al, 114 and Das et al 115 The effect of surface properties on DOPA adhesion Recently, using scanning tunnel microscopy (STM), Li et al found that DOPA showed different binding status and movement modes on the crystal rutile h110i surface. 116 The surface hydroxyl group greatly enhanced the diffusion ability of absorbed catechols.…”
Section: Single-molecule Force Spectroscopy Experiments By Afmmentioning
confidence: 99%
“…Quinones provide opportunities for adhesion to amine-functionalized (e.g. protein) surfaces, where the force to break (∼2 nN) is consistent with formation of a covalent interfacial quinone-amine adduct (Lee et al, 2006;Utzig et al, 2016). Such adducts, however, are unlikely to form in the highly reducing environment of the plaque interface.…”
Section: Adhesion Reconciled With Biology and Chemistrymentioning
confidence: 99%